The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.15604
|View full text |Cite
|
Sign up to set email alerts
|

NUSAP1 promotes invasion and metastasis of prostate cancer

Abstract: We have previously identified nucleolar and spindle associated protein 1 (NUSAP1) as a prognostic biomarker in early stage prostate cancer. To better understand the role of NUSAP1 in prostate cancer progression, we tested the effects of increased and decreased NUSAP1 expression in cell lines, in vivo models, and patient samples. NUSAP1 promotes invasion, migration, and metastasis, possibly by modulating family with sequence similarity 101 member B (FAM101B), a transforming growth factor beta 1 (TGFβ1) signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 61 publications
(91 reference statements)
3
64
0
Order By: Relevance
“…Okamoto et al revealed high NUSAP1 expression was related to more advanced T stage and inhibiting NUSAP1 resulted in the suppression of cell proliferation in Oral Squamous Cell Carcinoma (OSCC). Similar biological functions of NUSAP1 were also observed in other malignancies, including breast cancer, hepatocellular carcinoma (HCC), glioblastoma multiforme (GBM), colorectal cancer, astrocytoma, glioma, renal cell carcinoma, and prostate cancer . And previous studies also reported downregulating NUSAP1 could enhance the susceptibility to epirubicin in invasive breast cancer and the anti‐tumour effect of paclitaxel in OSCC .…”
Section: Introductionsupporting
confidence: 59%
“…Okamoto et al revealed high NUSAP1 expression was related to more advanced T stage and inhibiting NUSAP1 resulted in the suppression of cell proliferation in Oral Squamous Cell Carcinoma (OSCC). Similar biological functions of NUSAP1 were also observed in other malignancies, including breast cancer, hepatocellular carcinoma (HCC), glioblastoma multiforme (GBM), colorectal cancer, astrocytoma, glioma, renal cell carcinoma, and prostate cancer . And previous studies also reported downregulating NUSAP1 could enhance the susceptibility to epirubicin in invasive breast cancer and the anti‐tumour effect of paclitaxel in OSCC .…”
Section: Introductionsupporting
confidence: 59%
“…NUSAP1 is a cell cycle-related protein that plays a key role in mitosis. It has been proved that NUSAP1 regulates apoptosis, proliferation, and metastasis [24]. Accumulating evidence reveals that NUSAP1 may serve as a biomarker for carcinogenesis and cancer progression [25].…”
Section: Discussionmentioning
confidence: 99%
“…NUSAP1 overexpression has been described in bladder, cervix, colon, glioblastoma, liver, lung, oral squamous cell carcinoma, prostrate, kidney, and breast [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] cancers. Multiple studies have correlated its over-expression with a poor prognosis [22,28,30,32,36,37,40,41]. Zhang et al [37] demonstrated that down-regulation of NUSAP1 suppressed proliferation, migration and invasion of MCF7 cells by disturbing the regulation of CDK1 and DLGAP5, and reported increased susceptibility to epirubicin [37].…”
Section: Discussionmentioning
confidence: 99%